The synthesis strategies and photocatalytic performances of TiO2/MOFs composites: A state-of-the-art review - Chong-Chen Wang; Xun Wang; Liu, Wen (Chemical Engineering Journal, 2020)
Up to now, titanium dioxide (TiO2) is the most established semiconductor photocatalyst, which is used to achieve photocatalytic H2 evolution, pollutants degradation, CO2 reduction, and N2 reduction under UV light irradiation. TiO2 as photocatalyst is always under the spotlight due to its unique properties like outstanding thermal/chemical stability, wide bandgap with suitable band edge, low cost, non-toxicity, and corrosion resistance. To further improve the photocatalytic activity of TiO2, the versatile and porous metal-organic frameworks (MOFs) can be introduced to constructionTiO2/MOF composites, which can accomplish the enhanced light absorption performance and improved electron-hole pair separation. With this review, the fabrication strategies, characterizations techniques, photocatalytic activities and the mechanisms of some selected TiO2/MOF composites were reviewed and highlighted. The last but not the least, the outlooks and challenges of TiO2/MOF composites as photocatalysts for energy conversion and environment remediation are proposed.
Keywords: composite; Metal-organic frameworks; Photocatalysis; Synthesis; Titanium dioxide